Efforts to Improve the Character of Manners through Habituation of Javanese Language - Mukhamat Saini; Sabrina Marta Putri; Achmad Fauzan; Arizqi Ihsan Pratama; Didin Sirojudin (STAI Miftahul Ula Nganjuk, 2025)
The Javanese language, particularly Krama Inggil, plays a crucial role in the formation of cultural identity and polite behavior among Javanese communities. This study aims to enhance the courtesy character of fourth-grade students at MI Da'watul Khoir Kedungringin Drenges Kertosono through the habituation of the Javanese Krama Inggil language. A qualitative research method was employed, utilizing observation, interviews, and documentation for data collection. The results indicate that the habituation process, including regular use of Krama Inggil in communication, wearing traditional surja clothing, and integration of local language content into the curriculum, significantly contributes to the development of courteous behavior. Supporting factors include active student participation, parental involvement, and the availability of adequate resources, while challenges include inconsistent language use at home and occasional lapses by teachers. The study concludes that systematic habituation of Krama Inggil fosters a respectful and courteous character among students.